THE EXISTENCE OF MEDIATING JUDGES IN THE PROCESS OF CIVIL DISPUTE MEDIATION BASED ON THE SUPREME COURT REGULATION NO. 1 YEAR 2016 - Wahyudi Kurniawan (Legal Standing : Jurnal Ilmu Hukum, 2019)
The aims of this research are 1) to analyze the existence of mediating judges in the process of civil dispute mediation based on the Supreme Court Regulation (Peraturan Mahkamah Agung/PERMA) No. 1 year 2016 regarding the mediation procedures in court; 2) to analyze the supporting and the inhibiting factors which influence the existence of mediating judges in the process of civil dispute mediation in court.  This research is a normative juridical study with primary, secondary, and tertiary law materials. The manner and the instruments to collect the legal materials are using the method of documentation and document study. Data analysis is done by analyzing the research materials qualitatively.  The research results and discussion show that the existence of mediating judges in the process of civil dispute mediation based on the Supreme CourtRegulation No. 1 year 2016 regarding the mediation procedures in court becomes  the main choice of the parties who are in dispute. The supporting factors of the mediation by the mediating judges in a civil dispute are: human resources, economical budget, and infrastructure. The inhibiting factors of mediation by mediating judges in civil law disputes are: the parties are not present during the mediation, the number of certificated judges, and the society’s knowledge. Based on the research results and the discussion, it can be concluded that: 1) the mediation process by the mediating judges in the solving of civil law disputes becomes the main choice of the conflicting parties, 2) the supporting and the inhibiting factors which influence the existence of mediating judges in the processof mediating civil disputes are as follows: human resources, level of knowledge or  the society’s understanding, facilities and infrastructure, work burden of the judges, also the regulations in the implementation of the mediation. Suggestions regarding the results of this research are: 1) increasing the service of the mediation process by the mediating judges in court, 2) increasing the quality of the human resources, increasing the facilities and the infrastructure regarding mediation, 3) and increasing the socialization to the people regarding mediation and also the issuing of regulations on mediation which are more complete and detailed.